The Relationship between Maternal Pre-Pregnancy BMI and Preschool Obesity - Susan L. Averett; Erin K. Fletcher (Institute for the Study of Labor (IZA), 2015)
The increasing prevalence of obesity during pregnancy raises concerns over the intergenerational transmission of obesity and its potential to exacerbate the current obesity epidemic. The fetal origins hypothesis posits that the intrauterine environment might have lasting effects on children's outcomes. A large literature establishes that mother's pre-pregnancy obesity is correlated with obesity in her children. However, previous research is largely based on comparing individuals across families and hence cannot control for unobservable factors associated with both maternal and child obesity. We use both within-family comparisons and an instrumental variable approach on a sample of 4435 children to identify the effect of maternal pre-pregnancy obesity on obesity in preschool-aged children. Consistent with extant research, OLS models that rely on across-family comparisons indicate a significant correlation between maternal pre-pregnancy obesity and preschool obesity. However, maternal fixed effects render those associations insignificant. Instrumenting for mother's BMI with her sisters' BMI values confirms the null result indicating that the in utero transmission of obesity is likely not driving the increase in childhood obesity.
Keywords: I12; J13; 330; preschool obesity; pre-pregnancy obesity; gestational weight gain